THE EFFECT PROFITABILITY, FIRM SIZE AND LIQUIDITY: TOWARDS CAPITAL STRUCTURE - Putra, Krisanta Sumardi; Tarigan, Lukas; Panjaitan, Robert (Universitas Kristen Indonesia, 2017)
This research aimed to knowing the influence Profitability, Firm Size and liquidity of capital structure. The population in this research are all Manufacturing company cement industry sub-sector on LQ45 listed on the BEI from 2006 to 2015 period. This type of sampling in this research using purposive sampling technique. The data used in this research is secondary published data. The results showed that the Profitability has no effect on cement industry sub sector manufacture capital structure in 2006-2015, Firm size has effect on capital structure in the 2006-2015. Manufacturing company cement industry sub-sector, while Liquidity has no effect on cement industry sub sector manufacture capital structure in 2006-2015.Keywords: Manufacturing Companies cement industry sub-sector, Return on Equity, Debt To Equity, Firm size, liquidity.